Rhenium in Indian rivers: Sources, fluxes, and contribution to oceanic budget - Waliur Rahaman; Sunil Kumar Singh; Anil Dutt Shukla (Geochemistry, Geophysics, Geosystems)
The abundance and distribution of dissolved and particulate Rhenium (Re) has been measured in several rivers draining the Himalaya and Peninsular India, from their origin to outflow into the Bay of Bengal and the Arabian Sea. The large data set resulting from this study on rivers flowing through a variety of lithologies e.g., the crystallines and sediments of the Himalaya, Deccan basalts, Vindhyan sediments and the Indian shield significantly enhances our understanding of the aqueous geochemistry of Re and also constrains its sources to rivers and fluxes to the sea. The concentration of dissolved Re in rivers of the Himalaya and the Peninsular India shows wide range; 1.4 to 72.7 pmol/kg (mean 7.8 pmol/kg) and 0.5 to 122 pmol/kg (mean 15 pmol/kg) respectively. The discharge weighted average annual flux of dissolved Re transported by the rivers from these regions are ∼5800 and ∼15,700 mol/year respectively. The major source of dissolved Re, as determined from inter‐element associations, is black shales for the Himalayan rivers and pyrites in basalts for the east flowing Deccan rivers. In addition, there are evidences of considerable anthropogenic supply of Re to some of the rivers that have very high Re concentrations. Estimates of anthropogenic supply based on their Re/K ratios suggest that this source accounts for most of the Re in the Peninsular rivers, particularly the Godavari. The annual flux of anthropogenic Re transported by the Peninsular rivers is ∼14,600 mol, most of which is from the Godavari. This anthropogenic flux accounts for ∼70% of the total Re supply by the Indian rivers to the adjacent seas and 3.4% of the global riverine flux to the oceans. The global average, pre‐anthropogenic (natural) concentration of dissolved Re in rivers is estimated to be ∼3 pmol/kg based on Re−K correlation. This value is much lower than the contemporary average determined from the measured concentrations and earlier estimate of natural Re based on Re−SO4 link.